2020
DOI: 10.1177/1077559520926568
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Economic Pressure, Financial Assistance, and Children’s Behavioral Health in Kinship Care

Abstract: About half of kinship families live in poverty, and one third of them receive financial assistance such as Temporary Assistance for Needy Families (TANF) and foster care payments. This study selected children who remained in kinship care ( N = 267) for three waves from nationally representative data and examined the longitudinal associations among poverty, economic pressure, financial assistance, and children’s behavioral health outcomes in kinship care. Results from multilevel mixed-effects generalized linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…For example, as part of the policies on childcare, modalities on parent–caregiver relationships could be spelled out as well as plans for child welfare workers to supervise and regularly monitor the welfare of children in kinship care. Similar to other studies (Montserrat, 2014; Xu, Bright, Ahn, Huang, & Shaw, 2020; Xu, Bright, Barth, & Ahn, 2020), it has been revealed that the training of kinship caregivers is key to ensuring the welfare of children in care. The call by young people in this study to include the training in childcare policies suggests the lack of adequate knowledge and skills among the caregivers in meeting the needs of children in kinship care.…”
Section: Discussionsupporting
confidence: 76%
“…For example, as part of the policies on childcare, modalities on parent–caregiver relationships could be spelled out as well as plans for child welfare workers to supervise and regularly monitor the welfare of children in kinship care. Similar to other studies (Montserrat, 2014; Xu, Bright, Ahn, Huang, & Shaw, 2020; Xu, Bright, Barth, & Ahn, 2020), it has been revealed that the training of kinship caregivers is key to ensuring the welfare of children in care. The call by young people in this study to include the training in childcare policies suggests the lack of adequate knowledge and skills among the caregivers in meeting the needs of children in kinship care.…”
Section: Discussionsupporting
confidence: 76%
“…This limitation may not be overcome because there is no representative sampling frame for grandparent kinship providers, as previous studies also used a convenience sampling method ( Lee et al, 2016 ). Previous studies (e.g., Xu, Bright, Barth et al, 2020 ) based on the second National Survey of Child and Adolescent Well-Being (NSCAW II), a nationally representative study, found that kinship caregivers’ average age was 50 years old, 91.76 % were female, about half were married, and 32 % had high school or more education, 43.5 % were employed, and 52 % lived below the federal poverty line. Because of the nature of a convenience sample and an online survey, selection bias may exist, which may lead to a skewed sample.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, about 7,249,122 grandparents live with their own grandchildren under 18 years old, and 34.8 % of them are responsible for grandchildren ( United States Census Bureau, 2012-2016 ). Grandparent kinship providers fall into this most vulnerable population mostly because of their age (e.g., 50 years), low socioeconomic status (e.g., 52 % lived below the poverty line), being a minority (e.g., 43.1 % minority), and having limited access to resources and support (e.g., received fewer financial support, parenting training, peer support groups, respite care support than foster parents; Sakai, Lin, & Flores, 2011 ; Xu, Bright, Barth, & Ahn, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health problems, such as depression and anxiety, are predicted to increase under the COVID-19 circumstance, particularly for those who have a history of mental health issues (Holmes et al, 2020). Similarly, one-third or more kinship families live below the federal poverty line (Ehrle & Geen, 2002;Y. Xu et al, 2021), and the pandemic has exacerbated financial hardship of these families.…”
mentioning
confidence: 99%